Adsorption and corrosion inhibition accomplishment for thiosemicarbazone derivatives for mild steel in 1.0 M HCl medium: Electrochemical, XPS and DFT studies - Zaidon, Fazhrul Haqimee; Kassim, Karimah; Mohd Zaki, Hamizah; Embong, Zaidi; Anouar, El Hassane (2021)
Four benzaldehyde thiosemicarbazone derivatives namely as 2-benzylidene-N-phenylhydrazinecarbothioamide (L1), 2-(4-hydroxybenzylidene)-N-phenylhydrazinecarbothioamide (L2), 2-(4-chlorobenzylidene)-Nphenylhydrazinecarbothioamide (L3), and 2-(4-methylbenzylidene)-N-phenylhydrazinecarbothioamide (L4) were successfully synthesized and elucidated by physical and spectral techniques, to be specific,melting point, elemental analysis (CHNS), infrared spectroscopy (FTIR) and 1H and 13C nuclear magnetic resonance spectroscopy (NMR). These organic corrosion inhibitors behaviour for mild steel (MS) in 1.0 M HCl solution was examined using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. Fromthe electrochemical measurements, most ligands behave as efficient inhibitors for theMS in 1.0MHCl solution which contribute the maximum inhibition efficiency up to 93.38% for L3. The potentiodynamic polarization measurements unfolds each synthesized compoundweremixed-type inhibitor based on the shifting of corrosion potentials (Ecorr) found to be lesser than±85 mV. The electrochemical impedance spectroscopy (EIS) analysis revealed retardation of metal corrosion succeeded by cause of adsorption of the four thiosemicarbazone derivatives inhibitor molecules at the metal/solution interface. The adsorption of thiosemicarbazone molecules on the low carbon steel surface in 1.0 M HCl solution obeys Langmuir adsorption isotherm. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) demonstrates in the presence of optimum concentration of L1-L4 inhibitors at 0.04mMindicates greatly reduced surface roughness ofMS in comparisonwith uninhibited solution. The findingswere further reinforced via surface elemental analysis ofmetal/solution interface viaX-ray Photoelectron Spectroscopy (XPS), which unveils L3 exhibit the greatest inhibition efficiency. The most plausible reason is due to benzene rings in the molecular structure increases the adsorption ability in supporting the substituent of chloro as well as conjugated double bond of C=N and C=S that chemisorbed along the surface of metal. The oxide species of FeO, Fe2O3 and FeOOH found to be chemisorbed and physisorbed on MS surface. The impact of molecular properties on the corrosion inhibition and the adsorbed sites of L1-L4 on the metal were investigated using density functional theory calculations (DFT) at the B3LYP/6–311+G (d,p) level of theory. Fromthe Frontier Molecular Orbitals (FMO), the Highest OccupiedMolecular Orbitals (HOMO) discloses adsorption of L2 on theMS surface generally due to 2-(4-hydroxybenzylidene)-N-hydrazinecarbothioamide, whereas for L1, L3 and L4 associated to the inclusion of phenyl carbothioamide. The Lowest Occupied Molecular Orbitals (LUMOs) of L1-L4 are comparatively resembling and delocalized of all molecules. DFT reveals protonated thiosemicarbazones exhibits high correlations coefficients as up to 99–100% in comparison to the corresponding neutral forms of themolecules. The increase in the inhibition efficiency of protonated L1, L2 and L3 is proportional to the ΔN and DM.